Surgical outcomes with high and low pulse energy femtosecond laser systems for cataract surgery - Lin, Hung-Yuan (Sci Rep, 2021)
Currently, there is no clear consensus in cataract surgery if low compared to high energy femto-lasers may enable better capsulotomy quality and induce lower inflammatory response. Therefore, the aim of this study was to compare the intra-operative outcomes achieved with high and low pulse energy femtosecond laser systems for cataract surgery. The charts of 200 eyes of 200 patients aged 68.3 ± 10.3 years who had undergone femtosecond laser-assisted cataract surgery using either group 1 high pulse energy: LenSx (Alcon Laboratories) (N = 100) or group 2 low pulse energy: FEMTO LDV Z8 (Ziemer) (N = 100) laser were reviewed retrospectively. Integrity of anterior capsulotomy, classified as (1) complete (free-floating or with minor microadhesions), (2) incomplete and (3) with capsular tears, intraoperative completeness of the clear corneal incisions (CCI, main incision and side port), incidences of intraoperative miosis and incidence of subconjunctival hemorrhage were evaluated and compared between the two groups. The proportion of complete capsulotomies was significantly higher in the group 2 than the group 1 (100% vs 94%; p = 0.03). The incidences of intraoperative miosis (0% vs 19%) and subconjunctival hemorrhage (1% vs 63%) were significantly lower in the group 2 than the group 1 (p < 0.001). Completeness of the main incision was comparable (97% vs 95%; p = 0.721) between the two groups. Although not statistically significant, the completeness of side-port incision was slightly better in the group 2 than the group 1 (91% vs 86%). Low energy laser system performed significantly better in terms of completeness of capsulotomy, intraoperative miosis and sub-conjunctival hemorrhage, compared with high energy laser; the CCI outcomes were comparable.